PENGARUH KESTABILAN LERENG TERHADAP KERENTANAN GERAKAN MASSA TANAH di SUB DAS PROGO HULU KABUPATEN TEMANGGUNG - , EUIS ETTY AL HAKIM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Progo Sub-Watershed Upstream is part of the Progo River basin, administratively located in Temanggung Regency, Central Java. This area is composed of Sindoro Volcanic Rock, Sumbing Volcanic Rock and Penyatan Formation. The purpose of this research was to know the stability of slope and the influence to vulnerability of mass movement and itâs pattern in Progo Sub- Watershed Upstream. This research used descriptive quantitative method to determine the stability of slope by provide assessments on any of the parameters that used. Descriptive qualitative method is used to determine the effect of slope stability to vulnerability of mass movement. The movement susceptibility distribution used spatial analysis method with geographic information system. The results of the study are largely in Progo Sub-Watershed Upstream has medium levels of slope stability, there area of 23.569 ha, located on D2.II.P.Lckm, D2.II.K.Lckm, Vsm1.V.K.Ac, Vsm2.IV.SH.Li, Vsm3.II.SH.Lc, Vsm3.II.TL.Lck, D1.III.K.Rckb, D1.III.TL.Lck, D1.IV.TL.Lckm, D3.III.K.Rckb, D1.III.K.Lckm, Vsd1.V.B.Rckm, Vsd1.V.TL.Rckm, Vsd2.IV.K.Rckm, Vsd2.IV.TL.Rckm, Vsd2.III.SH.Ac, Vsd2.III.SH.Rckn, Vsd4.I.P.Lc, Vsd4.I.S.Lc, Vsd3.II.SH.Ac dan Vsd3.II.S.Ac. High levels of slope stability are covering 5.828 ha on Vsd4.I.S.Lck, Vsm3.II.P.Lck dan Vsd4.I.P.Lck. In Vsm1.V.B.Ac have low levels and there area 355 ha. The mass mvement in research are has influenced by low levels of slope stability, high to very high levels of rainfalls and intencity characteristics physical. The pattern of distribution mass movement is continuous with spread of slope stability, rainfalls intencity and human activity effect in characteristic phisycal of slope.